Diachronic Study on the Origin of Mongolian word алим “apple” in Terms of Phonology, Morphology, Semantics and Linguistic Distribution - Shigeki, Shiotani (Altaica, 2024)
In this paper we attempted to find out the origin of Mongolian word алим “apple” in terms of phonology, morphology, semantics and linguistic distribution. As a result of the research, some points were made clear as follows: 1. The Written Mongolian form alima “apple” comes from the word of Ancient Turkic almïla ~ alma “apple”, which has a strong possibility of being the borrowing word of Proto-Indo-European language form *ab(e)l-, because both the Ancient Turkic and PIE forms have the word-initial vowel a- and second syllabic-initial consonant being bilabial b(~ p), m plus liquid sound l in common. In other words the Mongolin form alima “apple” is in its PIE origin through the Ancient Turkic language. 2. The Minhe Monguor form amula probably comes from either the metathesis form of the Mongolian form alima within the Mongolic languages, or comes from the haplology form of the Ancient Turkic form almïla (> *amïla > *amila > amula). 3. From the perspective of meaning within the Mongolic languages, the form alima first appears in alima “梨 pear” in Middle Mongolian, and the Modern Central Mongolian dialects such as Khalkha Mongolian, Buryat and Kalmyk languages have the meaning “apple”, while Inner Mongolian, Oirad Mongolian and Dagur languages have the meaning “pear”. In addition in the Mongolic isolated languages such as Baoan, Dongxiang, Kangjia, Monguor (Huzhu, Minhe), Shira Yugur they all have the general meaning “fruit” (broadening (generalization, or extension of meaning) from the meaning “pear” or “apple”). 4. As for the other Written Mongolian form ǰimis “fruit”, it comes from the Ancient Turkic form yemiš “fruit” (< *ǰemiš) which also appears in Middle Mongolian and only spreads in some Modern Central Mongolian dialects, but not at all in the Mongolic isolated languages such as Baoan, Dongxiang, Kangjia, Monguor (Huzhu, Minhe), Shira Yugur, and Dagur languages. 5.In terms of semantic changes in Inner Mongolian dialects, the Mongolian form alima, which used to mean “pear” in Middle Mongolian, is used to mean “pear” as before. To avoid homonymic collisions which distinguish alma “apple” from alima “pear”, the form “apple” came to be used as the derivative word almarad that has the same stem alma “apple”. 6. In Khalkha Mongolian dialect, the meaning of the Mongolian form alima was slightly changed to “apple” from “pear” with the appearance of the Chinese loanword liir (лийр) “pear” to avoid semantic collisions between them. Монгол хэлний “алим” гэдэг үгийн гарал үүслийг тус үгийн авиа, хэлбэр, утга болон хэлний тархцын талаар цуваа цагийн үүднээс судалж үзсэн нь